Boulevard Saint-Laurent, la Main de Montréal et son Opéra numérique surréaliste en trois actes. Une histoire d’exposition - Sylvie Durand (Conserveries Mémorielles)
For many years now, history museums in Quebec have integrated films in their exhibition rounds from various types: short features, sequences of archives or interactive editings. Using such filmic tools modulates the organization of the visit, allowing to contextualize and humanize the historical subject.As a museographer I promoted the integration of films in several exhibition displays. Using a concrete example, Saint-Laurent, the "hand" of Montreal, I explain the design process that led the team to create a contemporary short film within an exhibition history.